Chickens tackle ticks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
A common sight in Africa and Asia is to see cattle and wild buffalo roaming about with birds such as cattle egrets or oxpeckersperched on their backs. These birds are providing a vital service in keeping the animals free of ticks. In Kenya,...